Do fiscal imbalances deteriorate sovereign debt ratings? - Afonso, António (2011)
We use sovereign debt rating estimations from Afonso, Gomes and Rother (2009, 2010) for Fitch, Moody’s, and Standard & Poor’s, to assess to what extent the recent fiscal imbalances are being reflected on the sovereign debt notations. We use macro and fiscal data up to 2009, and macro and fiscal projections, to obtain the expected rating for several OECD countries. The answer to the title question is yes, but in a diverse way for each country. Our average model predictions point to a heterogeneous behaviour of rating agencies across countries.